The Importance of Education Facility as Sustainable Urban Generation Tool - Fritz Akhmad Nuzir; Haris Murwadi; Bart Julien Dewancker (International Conference on Engineering and Technology Development (ICETD), 2013)
Education value has always been a part of urban development since the age of ancient Greece, Rome, India, and China. It is recognized as the changing factor into a civilization society. Every society in the world has at least the simplest form of education which is at home. Meanwhile many others have been utilizing this value to a greater purpose of the community through the development of education facilities. One of the education facilities that contribute substantially to the development of an urban area is higher education institute or university.According the Brundtland Commission, sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Therefore a sustainable urban generation tool is a feature that is expected to generate the development of an urban area inorder to meet the definition above. Sustainable development has many criteria such as economy (growth of annual income), social (growth of public participation and awareness),and the most important, environment (growth of facility/infrastructure and ecological management). Japan as a country which has limited natural resources, has been experiencing aging population and declining on birthrate. Therefore in order to maintain its economic growth, Japan is using its science and technology advantages as its main generator. Meanwhile, it is acknowledged that science and technology are the outcomes of education process. So at the end of the day, education in Japan plays important roles in the development of the economy and the society. This paper aims to acknowledge the importance of education facility as sustainable urban generation tool by studying thedevelopment of the economy, social, and environment of the case study area which is the Kitakyushu Science Research and Park in Kitakyushu (Japan).